Influence of molybdenum on haematological indices in buffalo calves - VARUN, VARUN; SHARMA, SUMEET; SANDHU, H S; GOSAL, NAVJOT S (The Indian Journal of Animal Sciences, 2012)
An experimental trial was conducted on eight healthy buffalo calves aged between 6 and 12 months, divided into 2 groups equally. Group 1 calves served as healthy control while group 2 (treatment group) was administered sodium molybdate @ 30 mg/kg/day. Among group 2 calves daily administration of sodium molybdate for three consecutive weeks produced immediate alterations in various haematological parameters in comparison to healthy buffalo calves. Repeated oral administration of sodium molybdate in treatment group exerted profound anaemia and decline in the mean values of Hb, PCV, TLC, TEC, and MCH. However, no significant effect on values of ESR, MCHC and MCV was noticed. Thus to maintain the proper health and production in buffaloes exposure to excess dietary molybdenum should be avoided.